PERFORMANCE ANALYSIS OF SIMPANG EMPAT ROUNDABOUT IN BANJARBARU CITY - Wulandari, Agustina; Widayanti, Nova (Universitas Lambung Mangkurat, 2026)
The design of roundabout intersections is one of the vital aspects in the development of road networks, especially in areas with high traffic density from various directions. One of the roundabouts located in Banjarbaru City serves to serve the flow of vehicles from four main directions, namely Banjarbaru, Martapura, Sungai Ulin, and Cempaka. Along with the growth in population and motorized vehicles, traffic problems in the form of conflicts between vehicles and congestion are becoming increasingly complex at this location. The analysis method used refers to the 2023 Indonesian Road Capacity Guidelines (PKJI 2023) and analysis using Excel software. The data analyzed include the geometric aspects of the roundabout, traffic volume for 24 hours, and population data for Banjarbaru City. The results of the study showed that the existing conditions resulted in a degree of saturation (Ds) of 0.861, a delay (T) of 13.690 seconds/pcu, and a queue opportunity (Pa) of 51%, which indicates that the performance of the roundabout has decreased. After conducting repair simulations, there are two alternative solutions proposed, namely changing the roundabout into an intersection with traffic lights (APILL) which is able to reduce Ds to 0.721 and delay (T) to 11.51 seconds/pcu, as well as the option of widening the road geometry which produces Ds of 0.675, delay of 10.117 seconds/pcu, and the opportunity for queues to decrease to 26%. Keywords: roundabout, degree of saturation, delay, PKJI 2023, APILL intersection.